Assessment of Knowledge, Attitude, and Practice (KAP) towards Hypertension in the Elderlies - Rahmadia Kusumamardhika; Anis Puspita Utami; Hendro Darmawan (PT Kalbe Farma Tbk., 2023)
Introduction: The role of knowledge, attitude, and practice (KAP) in hypertension is crucial in controlling prevalence and preventing longterm complications against cardiovascular diseases. Method: Cross-sectional study on the elderlies with hypertension in Wijayakusuma Geriatric Outpatient Main Clinic, Bogor using valid KAP questionnaire. Results: The sample was 100 elderly hypertensive patients, 33% were male and 67% were female with an average of 67.43+5.13 years of age. As many as 75% of patients with controlled hypertension, 68% with obesity, 56% with hypertension less than 5 years, 54% had a family history of hypertension, and 2% had a history of smoking. The comorbidities were diabetes (40%), congestive heart disease (15%), and stroke (12%). The average knowledge is 81.88+16.8% (very good), the average attitude is 67.33+25.06% (good), and practice average 95+11.79% (very good). Knowledge is associated with education level (p=0.008) and hypertension duration (p=0.05). Attitudes are associated with controlled hypertension (p=0.008), whereas practice is related to age < 70 years (p=0.05). There is a relationship between knowledge and attitude (p=0.029). Conclusion: The role of KAP on hypertension in the elderly with hypertension are adequate, but can be improved. Pendahuluan: Peran pengetahuan, sikap, dan perilaku (PSP) pada hipertensi penting untuk mengontrol prevalensi dan mencegah komplikasi jangka panjang. Metode: Studi cross-sectional menggunakan kuesioner yang valid terkait PSP pada pasien lanjut usia (lansia) hipertensi di poliklinik Klinik Utama Geriatri Wijayakusuma, Bogor. Hasil: Didapatkan 100 orang pasien terdiri dari 33% laki-laki dan 67% perempuan dengan rerata umur 67,43±5,13 tahun. Sebanyak 75% pasien dengan hipertensi terkontrol, 68% dengan obesitas, 56% dengan hipertensi di bawah 5 tahun, 54% memiliki riwayat hipertensi pada keluarga, dan 2% dengan riwayat merokok. Komorbid adalah diabetes (40%), penyakit jantung kongestif (15%), dan stroke (12%). Rerata pengetahuan adalah 81,88±16,8% (sangat baik), rerata sikap adalah 67,33±25,06% (baik), dan rerata perilaku adalah 95±11,79% (sangat baik). Pengetahuan berkaitan dengan tingkat pendidikan (p=0,008) dan durasi hipertensi (p=0,05). Sikap berkaitan dengan hipertensi terkontrol (p=0,008) dan terkait pada kelompok usia ≤ 70 tahun (p=0,05). Terdapat hubungan antara pengetahuan dan sikap (p=0,029). Simpulan: Peran PSP terkait hipertensi pada lansia sudah adekuat tetapi dapat ditingkatkan.